Analisis Perencanaan Sistem Tenaga Listrik Untuk Keandalan Operasional CCTV Berbasis Energi Terbarukan - M Rizki Liano; Pristisal Wibowo; Muhammad Erpandi Dalimunthe (CV. Hawari, 2026)
Solar energy is a renewable energy source that can be effectively utilized to generate electricity through photovoltaic cells. This research aims to plan an off-grid Solar Power Plant (PLTS) at the Sejahtera Islamic Boarding School Multipurpose Building. The system is designed as an alternative energy source to ensure the continuous operation of a 24-hour CCTV security system. The methodology included literature studies, field observations, and data collection to design a reliable power system. Implementing a PLTS is highly recommended due to its minimal emissions and eco-friendly nature. Based on the planning and analysis, implementing this off-grid PLTS to support the operational reliability of the CCTV system is highly feasible. The research location possesses adequate solar potential, with an average sunlight duration of approximately 4.5 hours per day. This capacity is sufficient to meet the 24-hour electrical energy needs of the CCTV and its supporting devices. System planning demonstrates that the daily load requirement of 432 Wh can be fulfilled using one 100 Wp solar panel module, two 12 V 33 Ah batteries, a 500 W inverter, and a 20 A Solar Charge Controller (SCC). Ultimately, this off-grid PLTS ensures an uninterrupted electricity supply during PLN network outages. It serves as an environmentally friendly, economical, and sustainable solution to enhance CCTV-based security systems in Islamic boarding schools and similar facilities.